INTERNALIZATION OF STUDENT VALUES IN THE MODERN WORLD - Ahmad Hidayat; Aat Royhatudin (Cakrawala Pedagogik, 2021)
The background of this research is that santri as the sole heir in terms of receiving religious and Islamic mandates are less clear, even though the presence of Islam with the Koran is able to explain faith texts into a context of piety, but what is more basic is in understanding the narratives of its ideas as the form of his love for a kyai is in the santri, because the santri as the identity and scientific relay of a kyai in the present and in the future are able to continue the sustainability and sustainability of his spirituality and intellectuality, so that it is ensured that the friendly face and peace of the research are formulated how Islam through the identity of the santri is a representation Islam that has been produced through prophetic values, namely humanization, liberation and transcendence. These three values ??manifest and form in the realization and essence of God's light, from the spark of God's light descending to the Prophet as a form of God's authority by moving the rays of the process of humanization, liberation and transcendence as outlined in the form of exemplary attitudes of prophetic nature that have long been revealed which are then inherited. to the ulama so that their ability at the ushul stage is the knowledge of the essential truth from complete and comprehensive religious values, at the furu' santri stage at the scientific level practically as a mature change in teaching knowledge that can be utilized, this is no more as valid evidence that the existence of santri can revive the light of God and reassure in the midst of society and an increasingly modern world.